2004
DOI: 10.1038/sj.gt.3302276
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of genetically engineered mesenchymal stem cells in a rat glioma model

Abstract: The prognosis of patients with malignant glioma is extremely poor, despite the extensive surgical treatment that they receive and recent improvements in adjuvant radio-and chemotherapy. In the present study, we propose the use of gene-modified mesenchymal stem cells (MSCs) as a new tool for gene therapy of malignant brain neoplasms. Primary MSCs isolated from Fischer 344 rats possessed excellent migratory ability and exerted inhibitory effects on the proliferation of 9L glioma cell in vitro. We also confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
432
3
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(477 citation statements)
references
References 47 publications
22
432
3
11
Order By: Relevance
“…37,38 Several studies with transplantable tumors in mice have shown homing of MSC to many different cancers. [39][40][41][42] As better understanding of the biology of MSC and cancer cell interaction is growing, many studies have successfully employed bone marrow-derived MSC as therapeutic agents to treat a wide range of cancers.…”
Section: Msc In Cancer Therapymentioning
confidence: 99%
“…37,38 Several studies with transplantable tumors in mice have shown homing of MSC to many different cancers. [39][40][41][42] As better understanding of the biology of MSC and cancer cell interaction is growing, many studies have successfully employed bone marrow-derived MSC as therapeutic agents to treat a wide range of cancers.…”
Section: Msc In Cancer Therapymentioning
confidence: 99%
“…In addition, gene-modification of MSCs by infection with an adenoviral vectorencoding human interleukin-2 enhanced the antitumor effect and further prolonged survival. 83 Combination of suppression of miR-21 via locked nucleic acid (LNA)-antimiR-21 oligonucleotides and NSCs expressing a secretable variant of the cytotoxic agent tumor necrosis factor-related apoptosis-inducing ligand (S-TRAIL), led to a synergistic increase in caspase activity and decreased cell viability in human glioma cells in vitro and in vivo. 84 Although TRAIL selectively kills tumor cells, its short half-life, poor delivery and TRAIL-resistant tumor cells have diminished its clinical efficacy.…”
Section: Stem Cellsmentioning
confidence: 99%
“…16,25 To investigate whether the transduction with pHGCX HSV-1 amplicon viral vector will alter the tumor tropism of BM-hMSCs, in vitro migration chamber assays were performed. In the presence of either conditioned medium from NHAs or medium alone, both the naı¨ve and pHGCX-transduced BM-hMSCs did not migrate toward the underside of the membrane.…”
Section: Hsv-1-mediated Gene Transfer To Bm-hmscs Iaw Ho Et Almentioning
confidence: 99%
“…HSV-1 vectors have been widely used for gene delivery, especially to the brain due to its neurotrophic properties. 25 The recombinant HSV-1, either replication conditional or defective, contains the full viral genome with mutations in one or more viral genes. The replication-conditional recombinant HSV-1 viral vectors have been used to efficiently transduce neural precursor cells.…”
Section: Introductionmentioning
confidence: 99%